A method for preparing phenolic aerogel composite thermal insulation tile

Through plasma treatment to modify nano-silicon carbide whiskers and chopped carbon fibers, combined with the processing technology of sol coating liquid and silane coupling agent, the problems of brittleness, bonding performance and thermal stress of existing insulation tiles are solved. Significantly improve the temperature resistance, mechanical and thermal shock resistance of phenolic airgel composite insulation tiles.

CN119059795BActive Publication Date: 2025-01-21SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411553915.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-21
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing phenolic aerogel composite heat insulation tiles have shortcomings in improving material brittleness, avoiding brittle fracture, improving high-temperature protection durability, and reinforcing the bonding performance of the fiber framework and phenolic resin materials, and there are thermal stress problems, resulting in rapid temperature change process Cracks or deformations are easily generated in the middle, and the overall performance is reduced.

Method used

Plasma treatment is used to modify nano-silicon carbide whiskers and chopped carbon fibers to improve their surface roughness and specific surface area, and their bonding performance with the zirconia coating is enhanced through dipping coating and baking treatment in sol coating liquid. At the same time, a silane coupling agent is used to modify the surface of the polyimide fiber, and the mechanical properties and thermal insulation performance of the thermal insulation tiles are improved through the design of a composite molded body with a three-layer sandwich structure and impregnation shaping treatment.

Benefits of technology

It effectively improves the bonding performance of fiber skeleton and phenolic resin material, reduces the thermal stress problem of insulation tiles, avoids cracks or deformation during rapid temperature changes, and significantly improves the temperature resistance, mechanical properties and resistance of insulation tiles. Thermal shock performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a method for preparing a phenolic aerogel composite thermal insulation tile, belonging to the field of thermal insulation tiles. The method for preparing the phenolic aerogel composite thermal insulation tile consists of the following steps: preparing an outer layer molded body, preparing a modified reinforcing fiber, preparing a composite molded body, preparing an impregnation liquid, and impregnation shaping. The method for preparing the phenolic aerogel composite thermal insulation tile of the present invention can effectively improve the bonding performance between the fiber skeleton and the phenolic resin material while improving the brittleness of the material, avoiding brittle fracture, and improving the high-temperature protection durability; effectively reduce the thermal stress problem existing in the thermal insulation tile, avoid cracks or deformation of the thermal insulation tile during rapid temperature changes, and further improve the mechanical properties and thermal insulation properties of the thermal insulation tile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermal insulation tiles, and in particular to a method for preparing a phenolic aerogel composite thermal insulation tile. Background Art

[0002] With the advancement of aerospace technology, the research on spacecraft has been heating up in recent years. From space shuttles to reusable carriers to hypersonic vehicles, when flying through the atmosphere, due to the friction between the surface of the vehicle and the surrounding air and the compression of the air in front, the spacecraft will be subjected to severe aerodynamic heating, high temperature and structural thermal stress. This complex flight environment requires the spacecraft itself to have good thermal insulation performance to ensure the stability of the internal system of the spacecraft and the safety of personnel. Based on this, in order to ensure the flight safety and flight stability of the spacecraft, it also puts forward higher requirements for the performance of the thermal insulation materials on the outer surface of the spacecraft.

[0003] In the prior art, the thermal insulation material on the outer surface of aerospace vehicles is generally thermal insulation tiles, which have the advantages of light weight, good thermal insulation performance, and high temperature resistance. The use of thermal insulation tiles can control and block the heat transferred from the surface of the aerospace vehicle to the inside, thereby effectively ensuring the stability of the external structure of the aerospace vehicle and the safety of internal equipment and personnel when the aerospace vehicle is flying for a long time. Phenolic resin-based thermal insulation materials are a type of composite thermal insulation material commonly used in aerospace vehicles. They have the advantages of fire retardancy and ablation resistance. However, phenolic resin-based materials are relatively brittle and are prone to brittle fracture when subjected to impact or vibration loads during the flight of the aerospace vehicle; and their high-temperature protection durability is poor, and they are prone to powderization and failure.

[0004] In order to overcome the above defects, the prior art usually uses a fiber skeleton as a supporting material, combines the fiber skeleton material with a phenolic resin material, and prepares a composite thermal insulation tile. Through the supporting effect of the fiber skeleton in the composite thermal insulation tile, combined with the thermal insulation and protection performance of the phenolic resin material, better thermal insulation and protection performance is achieved. However, the combination performance of the fiber skeleton and the phenolic resin material is not good, and the prepared thermal insulation tile has a thermal stress problem. It is easy to crack or deform during the rapid temperature change of the thermal insulation tile, and the overall performance is greatly reduced; and it limits the further improvement of the mechanical properties and thermal insulation performance of the thermal insulation tile.

[0005] It can be seen that the existing phenolic aerogel composite insulation tiles cannot effectively improve the bonding performance between the fiber skeleton and the phenolic resin material while improving the brittleness of the material, avoiding brittle fracture, and improving the high-temperature protection durability; it cannot effectively reduce the thermal stress problem existing in the insulation tiles, and further improve the mechanical properties and thermal insulation properties of the insulation tiles. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing a phenolic aerogel composite thermal insulation tile, which can effectively improve the bonding performance between the fiber skeleton and the phenolic resin material while improving the brittleness of the material, avoiding brittle fracture, and improving the high-temperature protection durability; effectively reduce the thermal stress problem existing in the thermal insulation tile, avoid cracks or deformation of the thermal insulation tile during rapid temperature changes, and further improve the mechanical properties and thermal insulation properties of the thermal insulation tile.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a phenolic aerogel composite heat-insulating tile comprises the following steps: preparing an outer layer forming body, preparing modified reinforcing fibers, preparing a composite forming body, preparing an impregnation liquid, and impregnating and shaping.

[0009] The preparation of the outer layer molded body comprises the following steps: pre-modification and composite molding.

[0010] The pre-modification method comprises the following steps: placing nano silicon carbide whiskers and chopped carbon fibers in a plasma treatment device respectively, maintaining the distance between the nano silicon carbide whiskers and the chopped carbon fibers and the discharge center in the plasma treatment device at 12-15 cm; using argon gas to completely replace the air in the plasma treatment device, then controlling the argon gas introduction rate to 0.6-0.7 L / min, the plasma treatment frequency to 3-4 MHz, the discharge power to 300-400 W, and performing plasma treatment for 10-15 minutes, thereby respectively obtaining pre-modified nano silicon carbide whiskers and pre-modified chopped carbon fibers.

[0011] In the pre-modification, the diameter of the nano-SiC whiskers is 100-120 nm and the length is 35-40 μm;

[0012] The diameter of the chopped carbon fibers is 450-500 nm and the length is 10-13 mm.

[0013] The composite molding method comprises the following steps: adding nano lightweight magnesium oxide, yttrium oxide and octadecyl magnesium chloride into zirconium oxide sol, performing ultrasonic dispersion for 10-20 minutes, and stirring for 30-40 minutes to obtain a sol coating liquid; adding pre-modified nano silicon carbide whiskers and pre-modified chopped carbon fibers into the sol coating liquid, stirring for 20-30 minutes, and then standing and impregnating for 2-3 hours to obtain a mixed slurry; introducing the mixed slurry into a mold, performing suction filtration molding, and controlling the molding thickness to be 12-15 mm to obtain a molded body; then placing the mold containing the molded body into a vacuum drying oven, drying at 100-105° C. for 22-24 hours in a vacuum environment of 0.08-0.09 MPa, and demolding; then transferring the mold into a roasting furnace, heating to 240-260° C. at a heating rate of 0.8-0.9° C. / min, roasting at the temperature for 70-90 minutes, and cooling to room temperature with the furnace to obtain an outer layer molded body.

[0014] In the composite molding, the weight ratio of the modified nano silicon carbide whisker, the pre-modified chopped carbon fiber, and the sol coating liquid is 3.5-4:1.2-1.5:35-40;

[0015] The concentration of zirconium oxychloride in the zirconium oxide sol is 0.25-0.3 mol / L;

[0016] The weight ratio of nano lightweight magnesium oxide, yttrium oxide, octadecyl magnesium chloride and zirconium oxide sol is 3.5-4:0.15-0.18:0.5-0.6:100;

[0017] The average particle size of nano lightweight magnesium oxide is 20-25nm.

[0018] The method for preparing the modified reinforced fiber comprises the following steps: adding the polyimide fiber to an ethanol solution with a volume concentration of 75-80%, ultrasonically dispersing the solution for 10-20 minutes, oscillating and heating the solution to 45-50° C., and dripping the silane coupling agent A-171 while maintaining the temperature; controlling the dripping time of the silane coupling agent A-171 to be 40-60 minutes; after the dripping is completed, continuing the heat preservation treatment for 4-5 hours, separating the solid matter, and then placing the solid matter in a vacuum drying oven, and drying the solid matter at 75-80° C. to a constant weight in a vacuum environment of 0.08-0.09 MPa to obtain the modified reinforced fiber.

[0019] In the preparation of the modified reinforced fiber, the weight ratio of the polyimide fiber, the ethanol solution, and the silane coupling agent A-171 is 8-9:100:1.5-1.8;

[0020] The diameter of the polyimide fiber is 6-7 μm and the length is 10-13 mm.

[0021] The method for preparing the composite molded body comprises: laying the modified reinforcing fiber on the outer layer molded body, and controlling the thickness of the layer to be 8-10 mm, and forming a modified reinforcing fiber layer after the layering is completed; then placing an outer layer molded body on the modified reinforcing fiber layer to obtain a preformed body with a three-layer sandwich structure, wherein the lower layer is the outer layer molded body, the middle layer is the modified reinforcing fiber layer, and the upper layer is the outer layer molded body; the preformed body is impregnated with deionized water and then pressed, and then placed in a constant temperature box, heated to 100-105° C., and kept warm for 10-12 hours to obtain the composite molded body.

[0022] The method for preparing the impregnation solution is as follows: sodium bicarbonate, Tween-80 and nano-tantalum boride are added into deionized water, ultrasonically dispersed for 10-20 minutes, and then stirred for 30-40 minutes; phenolic resin is continuously added, and after uniform mixing, silane coupling agent KH-550 is continuously added, and stirred for 20-30 minutes to obtain the impregnation solution.

[0023] In the preparation of the impregnation solution, the weight ratio of sodium bicarbonate, Tween-80, nano-tantalum boride, deionized water, phenolic resin, and silane coupling agent KH-550 is 1.2-1.3:0.8-0.9:7-7.5:50-55:100-110:16-17;

[0024] The phenolic resin is a phenolic resin prepolymer with a molecular weight of 300-400;

[0025] The particle size of nano-tantalum boride is 40-50nm.

[0026] The impregnation shaping method comprises the following steps: impregnating the composite molded body into an impregnation liquid of 2-2.5 times the volume thereof, and performing vacuum impregnation for 50-60 minutes in a vacuum environment of 0.07-0.08 MPa. Then, the composite molded body is taken out and transferred into a constant temperature box, and after standing at room temperature for 10-12 hours, the composite molded body is heated to 90-95° C., kept warm and kept warm for 5-6 hours; the composite molded body is cooled to 40-45° C., kept warm and kept warm for 10-12 hours; the composite molded body is then transferred into a roasting furnace, and heated to 420-450° C. at a heating rate of 3-3.5° C. / min in an argon atmosphere environment, kept warm and roasted for 1.5-2 hours, and then cooled to room temperature with the furnace to obtain a phenolic aerogel composite thermal insulation tile.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The preparation method of the phenolic aerogel composite thermal insulation tile of the present invention comprises the following steps: in the step of preparing the outer layer molding body, the nano silicon carbide whiskers and the chopped carbon fibers are subjected to plasma treatment in an argon atmosphere environment, thereby increasing the surface roughness of the nano silicon carbide whiskers and the chopped carbon fibers and improving the specific surface area, thereby increasing the mechanical bite performance with the zirconium oxide coating in the subsequent composite molding step; and introducing a large number of active groups on the surface of the nano silicon carbide whiskers and the chopped carbon fibers, and improving the surface energy of the nano silicon carbide whiskers and the chopped carbon fibers, through the wetting and spreading effect of the sol coating liquid, and the chemical bonding effect. , further improving the bonding performance of nano silicon carbide whiskers and chopped carbon fibers with zirconium oxide coating; in the composite molding step, nano lightweight magnesium oxide, yttrium oxide, octadecyl magnesium chloride and zirconium oxide sol are used to prepare a sol coating liquid, and then the pre-modified nano silicon carbide whiskers and pre-modified chopped carbon fibers are impregnated and coated, and then filtered, formed, dried and calcined to obtain an outer layer molding; in the subsequent process of combining with phenolic aerogel, the phenolic aerogel can better penetrate into the pores of the zirconium oxide coating, thereby improving the bonding performance of the phenolic aerogel with the fiber skeleton, and through the zirconium oxide coating and the nano silicon carbide whiskers , chopped carbon fiber, and phenolic aerogel are combined to further improve the temperature resistance, mechanical properties, and thermal shock resistance of the thermal insulation tile, and improve the brittleness of the thermal insulation tile; in the step of preparing the modified reinforced fiber, the polyimide fiber is surface-modified with a silane coupling agent A-171 to improve the bonding performance between the polyimide fiber and the outer layer molding and the phenolic aerogel, improve the stability of the thermal insulation tile during rapid temperature changes, and further improve the brittleness of the thermal insulation tile to avoid brittle fracture; in the step of preparing the composite molding, a three-layer structure is provided in which the lower layer is the outer layer molding, the middle layer is the modified reinforced fiber layer, and the upper layer is the outer layer molding. The composite molded body is prepared by a layer sandwich structure; then in the step of preparing the impregnation solution, the phenolic aerogel and nano-tantalum boride are used to prepare the impregnation solution, and then the composite molded body is impregnated and molded. The aforementioned technical means cooperate with each other and work synergistically, which can improve the brittleness of the material, avoid brittle fracture, and improve the high-temperature protection durability, while effectively improving the bonding performance of the fiber skeleton and the phenolic resin material; effectively reduce the thermal stress problem of the insulation tile, avoid cracks or deformation of the insulation tile during rapid temperature change, have good high-temperature protection durability, and further improve the mechanical properties and thermal insulation properties of the insulation tile.

[0029] (2) The preparation method of the phenolic aerogel composite thermal insulation tile of the present invention, the thermal conductivity of the prepared phenolic aerogel composite thermal insulation tile is 0.048-0.050W / (m·K), the heat resistance temperature can reach 1050°C, the tensile strength is 27.9-28.3MPa, the compressive strength is 5.85-5.94MPa, and the fracture toughness is 0.53-0.56MPa·m 1 / 2The bonding strength between the fiber and the thermal insulation tile matrix is ​​2.3-2.4MPa, and there is no surface cracking or deformation of the phenolic aerogel composite thermal insulation tile.

[0030] (3) The preparation method of the phenolic aerogel composite thermal insulation tile of the present invention, after 20 rapid temperature change thermal shock cycles from 1000°C to room temperature, the tensile strength of the phenolic aerogel composite thermal insulation tile is 25.5-26.1MPa, the compressive strength is 5.42-5.51MPa, and the fracture toughness is 0.49-0.52MPa·m 1 / 2 The bonding strength between the fiber and the thermal insulation tile matrix is ​​2.1-2.2MPa, and there is no surface cracking or deformation of the phenolic aerogel composite thermal insulation tile.

[0031] (4) The preparation method of the phenolic aerogel composite thermal insulation tile of the present invention can effectively maintain the aerodynamic shape of the hypersonic aircraft, while effectively bearing aerodynamic heat, aerodynamic force and vibration, thereby achieving high reliability application of the thermal insulation tile. DETAILED DESCRIPTION

[0032] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0033] Example 1

[0034] This embodiment provides a method for preparing a phenolic aerogel composite thermal insulation tile, specifically:

[0035] 1. Preparation of outer layer molding

[0036] 1) Pre-modification

[0037] Nano silicon carbide whiskers and chopped carbon fibers were placed in a plasma treatment device respectively, and the distance between the nano silicon carbide whiskers, the chopped carbon fibers and the discharge center in the plasma treatment device was maintained at 12 cm; argon gas was used to completely replace the air in the plasma treatment device, and then the argon gas introduction rate was controlled to be 0.6 L / min, the plasma treatment frequency was 3 MHz, the discharge power was 300 W, and the plasma treatment was performed for 10 minutes to obtain pre-modified nano silicon carbide whiskers and pre-modified chopped carbon fibers respectively.

[0038] The diameter of the nano-SiC whisker is 110 nm and the length is 40 μm.

[0039] The diameter of the chopped carbon fibers was 470 nm and the length was 12 mm.

[0040] 2) Composite molding

[0041] Nano lightweight magnesium oxide, yttrium oxide and octadecyl magnesium chloride are added to zirconium oxide sol, ultrasonically dispersed for 10 minutes, and stirred for 30 minutes to obtain a sol coating liquid; pre-modified nano silicon carbide whiskers and pre-modified chopped carbon fibers are added to the sol coating liquid, stirred for 20 minutes, and then allowed to stand and immerse for 2 hours to obtain a mixed slurry; the mixed slurry is introduced into a mold, filtered and formed, and the forming thickness is controlled to be 12 mm to obtain a molded body; then the mold containing the molded body is placed in a vacuum drying oven, dried at 100°C for 22 hours in a vacuum environment of 0.08MPa, and demolded; then transferred to a roasting furnace, heated to 240°C at a heating rate of 0.8°C / min, kept warm and roasted for 70 minutes, and cooled to room temperature with the furnace to obtain an outer layer molded body.

[0042] The concentration of zirconium oxychloride in the zirconium oxide sol is 0.25 mol / L.

[0043] The weight ratio of nano lightweight magnesium oxide, yttrium oxide, octadecyl magnesium chloride and zirconium oxide sol in the sol coating liquid is 3.5:0.15:0.5:100.

[0044] The average particle size of nano lightweight magnesium oxide is 20nm.

[0045] The weight ratio of the modified nano silicon carbide whisker, the pre-modified chopped carbon fiber and the sol coating liquid is 3.5:1.2:35.

[0046] 2. Preparation of modified reinforcing fibers

[0047] The polyimide fiber was put into an ethanol solution with a volume concentration of 75%, and after ultrasonic dispersion for 10 minutes, the temperature was raised to 45°C by oscillation, and the silane coupling agent A-171 was added dropwise while keeping the temperature constant. The addition time of the silane coupling agent A-171 was controlled to be 40 minutes. After the addition was completed, the solution was kept warm for 4 hours, and the solid was separated and then placed in a vacuum drying oven. It was dried at 75°C to constant weight in a vacuum environment of 0.08 MPa to obtain a modified reinforced fiber.

[0048] Wherein, the weight ratio of polyimide fiber, ethanol solution and silane coupling agent A-171 is 8:100:1.5.

[0049] The diameter of the polyimide fiber was 6.5 μm and the length was 12 mm.

[0050] 3. Preparation of composite molding

[0051] The modified reinforcing fiber is laid on the outer layer molded body, and the thickness of the layer is controlled to be 8 mm. After the laying is completed, a modified reinforcing fiber layer is formed; then an outer layer molded body is placed on the modified reinforcing fiber layer to obtain a preform with a three-layer sandwich structure, in which the lower layer is the outer layer molded body, the middle layer is the modified reinforcing fiber layer, and the upper layer is the outer layer molded body; the preform is impregnated with deionized water and then pressed, and then placed in a constant temperature box, heated to 100°C, and kept warm for 10 hours to obtain a composite molded body.

[0052] 4. Preparation of impregnation solution

[0053] Sodium bicarbonate, Tween-80 and nano-tantalum boride were added to deionized water, ultrasonically dispersed for 10 minutes, and stirred for 30 minutes; phenolic resin was added, mixed evenly, and silane coupling agent KH-550 was added, stirred for 20 minutes to prepare an impregnation solution.

[0054] Among them, the weight ratio of sodium bicarbonate, Tween-80, nano-tantalum boride, deionized water, phenolic resin and silane coupling agent KH-550 is 1.2:0.8:7:50:100:16.

[0055] The phenolic resin is a phenolic resin prepolymer with a molecular weight of 350.

[0056] The particle size of nano-tantalum boride is 45nm.

[0057] 5. Dipping and shaping

[0058] The composite molded body was immersed in 2 times the volume of the impregnation liquid. After vacuum impregnation for 50 minutes in a vacuum environment of 0.07 MPa, the composite molded body was taken out and transferred to a constant temperature box. After standing at room temperature for 10 hours, the temperature was increased to 90°C and kept at this temperature for 5 hours; the temperature was lowered to 40°C and kept at this temperature for 10 hours; then the composite molded body was transferred to a calcination furnace. In an argon atmosphere, the temperature was increased to 420°C at a heating rate of 3°C / min, and the phenolic aerogel composite insulation tile was obtained after being calcined to room temperature with the furnace.

[0059] Example 2

[0060] This embodiment provides a method for preparing a phenolic aerogel composite thermal insulation tile, specifically:

[0061] 1. Preparation of outer layer molding

[0062] 1) Pre-modification

[0063] Nano-silicon carbide whiskers and chopped carbon fibers were placed in a plasma treatment device respectively, and the distance between the nano-silicon carbide whiskers, the chopped carbon fibers and the discharge center in the plasma treatment device was maintained at 13 cm; argon gas was used to completely replace the air in the plasma treatment device, and then the argon gas introduction rate was controlled to be 0.65 L / min, the plasma treatment frequency was 3.5 MHz, the discharge power was 350 W, and the plasma treatment was performed for 12 minutes to obtain pre-modified nano-silicon carbide whiskers and pre-modified chopped carbon fibers respectively.

[0064] The diameter of the nano-SiC whisker is 110 nm and the length is 40 μm.

[0065] The diameter of the chopped carbon fibers was 470 nm and the length was 12 mm.

[0066] 2) Composite molding

[0067] Nano lightweight magnesium oxide, yttrium oxide and octadecyl magnesium chloride are added to zirconium oxide sol, ultrasonically dispersed for 15 minutes, and stirred for 35 minutes to obtain a sol coating liquid; pre-modified nano silicon carbide whiskers and pre-modified chopped carbon fibers are added to the sol coating liquid, stirred for 25 minutes, and then allowed to stand and immerse for 2.5 hours to obtain a mixed slurry; the mixed slurry is introduced into a mold, filtered and formed, and the forming thickness is controlled to be 14 mm to obtain a molded body; the mold containing the molded body is then placed in a vacuum drying oven, dried at 102°C for 23 hours in a vacuum environment of 0.085MPa, and demolded; then transferred to a roasting furnace, heated to 250°C at a heating rate of 0.85°C / min, kept warm and roasted for 80 minutes, and cooled to room temperature with the furnace to obtain an outer layer molded body.

[0068] The concentration of zirconium oxychloride in the zirconium oxide sol is 0.28 mol / L.

[0069] The weight ratio of nano lightweight magnesium oxide, yttrium oxide, octadecyl magnesium chloride and zirconium oxide sol in the sol coating liquid is 3.7:0.16:0.55:100.

[0070] The average particle size of nano lightweight magnesium oxide is 20nm.

[0071] The weight ratio of the modified nano silicon carbide whisker, the pre-modified chopped carbon fiber and the sol coating liquid is 3.8:1.4:37.

[0072] 2. Preparation of modified reinforcing fibers

[0073] The polyimide fiber was put into an ethanol solution with a volume concentration of 78%, and after ultrasonic dispersion for 15 minutes, the temperature was raised to 48°C by oscillation, and the silane coupling agent A-171 was added dropwise while keeping the temperature constant. The addition time of the silane coupling agent A-171 was controlled to be 50 minutes. After the addition was completed, the solution was kept warm for 4.5 hours, the solid was separated, and then placed in a vacuum drying oven, and dried at 78°C to constant weight in a vacuum environment of 0.085 MPa to obtain a modified reinforced fiber.

[0074] Wherein, the weight ratio of polyimide fiber, ethanol solution and silane coupling agent A-171 is 8.5:100:1.7.

[0075] The diameter of the polyimide fiber was 6.5 μm and the length was 12 mm.

[0076] 3. Preparation of composite molding

[0077] The modified reinforcing fiber is laid on the outer layer molded body, and the layer thickness is controlled to be 9 mm. After the laying is completed, a modified reinforcing fiber layer is formed; then an outer layer molded body is placed on the modified reinforcing fiber layer to obtain a preform with a three-layer sandwich structure, in which the lower layer is the outer layer molded body, the middle layer is the modified reinforcing fiber layer, and the upper layer is the outer layer molded body; the preform is impregnated with deionized water and then pressed, and then placed in a constant temperature box, heated to 102°C, and kept warm for 11 hours to obtain a composite molded body.

[0078] 4. Preparation of impregnation solution

[0079] Sodium bicarbonate, Tween-80 and nano-tantalum boride were added to deionized water, ultrasonically dispersed for 15 minutes, and stirred for 35 minutes; phenolic resin was added, mixed evenly, and silane coupling agent KH-550 was added, stirred for 25 minutes to obtain an impregnation solution.

[0080] Among them, the weight ratio of sodium bicarbonate, Tween-80, nano-tantalum boride, deionized water, phenolic resin and silane coupling agent KH-550 is 1.25:0.85:7.3:52:105:16.5.

[0081] The phenolic resin is a phenolic resin prepolymer with a molecular weight of 350.

[0082] The particle size of nano-tantalum boride is 45nm.

[0083] 5. Dipping and shaping

[0084] The composite molded body was immersed in 2.2 times the volume of the impregnation liquid. After vacuum impregnation for 55 minutes in a vacuum environment of 0.075 MPa, the composite molded body was taken out and transferred to a constant temperature box. After standing at room temperature for 11 hours, the temperature was increased to 92°C and kept at this temperature for 5.5 hours; the temperature was lowered to 42°C and kept at this temperature for 11 hours; then the composite molded body was transferred to a roasting furnace. In an argon atmosphere, the temperature was increased to 430°C at a heating rate of 3.2°C / min, and the temperature was kept at this temperature for 1.8 hours. The composite molded body was cooled to room temperature with the furnace to obtain a phenolic aerogel composite insulation tile.

[0085] Example 3

[0086] This embodiment provides a method for preparing a phenolic aerogel composite thermal insulation tile, specifically:

[0087] 1. Preparation of outer layer molding

[0088] 1) Pre-modification

[0089] Nano-silicon carbide whiskers and chopped carbon fibers were placed in a plasma treatment device respectively, and the distance between the nano-silicon carbide whiskers, the chopped carbon fibers and the discharge center in the plasma treatment device was maintained at 15 cm; argon gas was used to completely replace the air in the plasma treatment device, and then the argon gas introduction rate was controlled to be 0.7 L / min, the plasma treatment frequency was 4 MHz, the discharge power was 400 W, and the plasma treatment was performed for 15 minutes to obtain pre-modified nano-silicon carbide whiskers and pre-modified chopped carbon fibers respectively.

[0090] The diameter of the nano-SiC whisker is 110 nm and the length is 40 μm.

[0091] The diameter of the chopped carbon fibers was 470 nm and the length was 12 mm.

[0092] 2) Composite molding

[0093] Add nano lightweight magnesium oxide, yttrium oxide and octadecyl magnesium chloride into zirconium oxide sol, ultrasonically disperse for 20 minutes, and stir for 40 minutes to obtain a sol coating liquid; add pre-modified nano silicon carbide whiskers and pre-modified chopped carbon fibers into the sol coating liquid, stir for 30 minutes, and then let it stand and immerse for 3 hours to obtain a mixed slurry; introduce the mixed slurry into a mold, filter and shape it, and control the molding thickness to be 15mm to obtain a molded body; then place the mold containing the molded body in a vacuum drying oven, dry it at 105°C for 24 hours in a vacuum environment of 0.09MPa, and demold it; then transfer it to a roasting furnace, heat it to 260°C at a heating rate of 0.9°C / min, keep it warm and roast it for 90 minutes, and cool it to room temperature with the furnace to obtain an outer layer molded body.

[0094] The concentration of zirconium oxychloride in the zirconium oxide sol is 0.3 mol / L.

[0095] The weight ratio of nano lightweight magnesium oxide, yttrium oxide, octadecyl magnesium chloride and zirconium oxide sol in the sol coating liquid is 4:0.18:0.6:100.

[0096] The average particle size of nano lightweight magnesium oxide is 20nm.

[0097] The weight ratio of the modified nano silicon carbide whisker, the pre-modified chopped carbon fiber and the sol coating liquid is 4:1.5:40.

[0098] 2. Preparation of modified reinforcing fibers

[0099] The polyimide fiber was put into an ethanol solution with a volume concentration of 80%, and after ultrasonic dispersion for 20 minutes, the temperature was raised to 50°C by oscillation, and the silane coupling agent A-171 was added dropwise while keeping the temperature constant. The addition time of the silane coupling agent A-171 was controlled to be 60 minutes. After the addition was completed, the solution was kept warm for 5 hours, and the solid was separated. It was then placed in a vacuum drying oven and dried at 80°C to constant weight in a vacuum environment of 0.09 MPa to obtain a modified reinforced fiber.

[0100] Wherein, the weight ratio of polyimide fiber, ethanol solution and silane coupling agent A-171 is 9:100:1.8.

[0101] The diameter of the polyimide fiber was 6.5 μm and the length was 12 mm.

[0102] 3. Preparation of composite molding

[0103] The modified reinforcing fiber is laid on the outer layer molded body, and the thickness of the layer is controlled to be 10 mm. After the laying is completed, a modified reinforcing fiber layer is formed; then an outer layer molded body is placed on the modified reinforcing fiber layer to obtain a preform with a three-layer sandwich structure, in which the lower layer is the outer layer molded body, the middle layer is the modified reinforcing fiber layer, and the upper layer is the outer layer molded body; the preform is impregnated with deionized water and then pressed, and then placed in a constant temperature box, heated to 105°C, and kept warm for 12 hours to obtain a composite molded body.

[0104] 4. Preparation of impregnation solution

[0105] Sodium bicarbonate, Tween-80 and nano-tantalum boride were added to deionized water, ultrasonically dispersed for 20 minutes, and stirred for 40 minutes; phenolic resin was added, mixed evenly, and silane coupling agent KH-550 was added, stirred for 30 minutes to prepare an impregnation solution.

[0106] Among them, the weight ratio of sodium bicarbonate, Tween-80, nano-tantalum boride, deionized water, phenolic resin and silane coupling agent KH-550 is 1.3:0.9:7.5:55:110:17.

[0107] The phenolic resin is a phenolic resin prepolymer with a molecular weight of 350.

[0108] The particle size of nano-tantalum boride is 45nm.

[0109] 5. Dipping and shaping

[0110] The composite molded body was immersed in 2.5 times the volume of the impregnation liquid. After vacuum impregnation for 60 minutes in a vacuum environment of 0.08 MPa, the composite molded body was taken out and transferred to a constant temperature box. After standing at room temperature for 12 hours, the temperature was increased to 95°C, and the temperature was kept at that temperature for 6 hours; the temperature was lowered to 45°C, and the temperature was kept at that temperature for 12 hours; then the composite molded body was transferred to a roasting furnace, and in an argon atmosphere, the temperature was increased to 450°C at a heating rate of 3.5°C / min, and the temperature was kept at that temperature for 2 hours. Then, the composite molded body was cooled to room temperature with the furnace to obtain a phenolic aerogel composite insulation tile.

[0111] Comparative Example 1

[0112] The technical solution of Example 2 is adopted, but the differences are: 1) the pre-modification step in preparing the outer molded body is omitted, and the nano silicon carbide whiskers and chopped carbon fibers are directly used in the subsequent composite molding step; 2) in the composite molding step, the addition of octadecyl magnesium chloride is omitted.

[0113] Comparative Example 2

[0114] The technical scheme of Example 2 is adopted, and its difference lies in: 1) the composite molding step in preparing the outer molded body is omitted, and in the step of preparing the composite molded body, pre-modified nano silicon carbide whiskers and pre-modified chopped carbon fibers are first used for mixed layering, and the layer thickness is controlled to be 13 mm. After obtaining the lower layer, modified reinforcing fibers are used for layering on the lower layer, and the layer thickness is controlled to be 9 mm. After obtaining the middle layer, pre-modified nano silicon carbide whiskers and pre-modified chopped carbon fibers are used for mixed layering, and the layer thickness is controlled to be 13 mm. After obtaining the upper layer, the preform is impregnated with deionized water and then pressed, and then placed in a constant temperature box, heated to 102°C, and kept warm for 11 hours to obtain a composite molded body; wherein, in the upper layer or the lower layer, the weight ratio of the pre-modified nano silicon carbide whiskers and the pre-modified chopped carbon fibers used is 3:1. 2) In the preparation of the impregnation solution, the addition of nano tantalum boride is omitted.

[0115] The preparation methods of the phenolic aerogel composite thermal insulation tiles of Examples 1-3 and Comparative Examples 1-2 were respectively used to test the thermal conductivity, heat resistance temperature, tensile strength, compressive strength, fracture toughness, and bonding strength between the fiber and the thermal insulation tile matrix of the prepared phenolic aerogel composite thermal insulation tiles; and the prepared phenolic aerogel composite thermal insulation tiles were observed to see whether surface cracks or deformation occurred.

[0116] Among them, the compressive strength is the non-destructive compressive strength data obtained by cyclic compression test under 40% compressive strain conditions; the fracture toughness is tested by the single-edge notched beam method (SENB method); the bonding strength between the fiber and the insulation tile matrix is ​​tested 20 times by the pull-out method, and the average value is taken.

[0117] The specific results are shown in the following table:

[0118]

[0119] Furthermore, the phenolic aerogel composite insulation tiles obtained in Examples 1-3 and Comparative Examples 1-2 were placed in a baking furnace, heated to 1000°C at a heating rate of 25°C / min in an air atmosphere, kept at that temperature for 6 hours, and then cooled to room temperature at a cooling rate of 25°C / min; the aforementioned rapid heating and cooling process was regarded as one thermal shock cycle, and after repeating it 20 times, the tensile strength, compressive strength, fracture toughness, and bonding strength between the fiber and the insulation tile matrix of each insulation tile were tested; and the phenolic aerogel composite insulation tiles were observed to see whether there were any surface cracks or deformations. The specific results are shown in the following table:

[0120]

[0121] It can be seen that the preparation method of the phenolic aerogel composite thermal insulation tile of the present invention, in the step of preparing the outer layer molding, plasma treatment is performed on the nano silicon carbide whiskers and chopped carbon fibers in an argon atmosphere environment, while increasing the surface roughness of the nano silicon carbide whiskers and the chopped carbon fibers, the specific surface area is increased, and the mechanical bite performance with the zirconium oxide coating in the subsequent composite molding step is increased; and a large number of active groups are introduced into the surface of the nano silicon carbide whiskers and the chopped carbon fibers, and the surface energy of the nano silicon carbide whiskers and the chopped carbon fibers is improved, through the wetting and spreading effect of the sol coating liquid, and the chemical bonding The invention relates to a method for preparing a composite coating liquid, wherein the composite coating liquid is prepared by combining nano-silicon carbide whiskers, chopped carbon fibers and zirconium oxide coatings with each other to further improve the bonding performance of the nano-silicon carbide whiskers and chopped carbon fibers with the zirconium oxide coating. In the composite molding step, nano-lightweight magnesium oxide, yttrium oxide and octadecyl magnesium chloride are used in combination with zirconium oxide sol to prepare a sol coating liquid, and then the pre-modified nano-silicon carbide whiskers and pre-modified chopped carbon fibers are impregnated and coated, and then filtered, formed, dried and calcined to obtain an outer layer molding. In the subsequent bonding process with phenolic aerogel, the phenolic aerogel can better penetrate into the pores of the zirconium oxide coating, thereby improving the bonding performance of the phenolic aerogel with the fiber skeleton, and through the bonding between the zirconium oxide coating and the nano- The combination of silicon carbide whiskers, chopped carbon fibers, and phenolic aerogel further improves the heat resistance, mechanical properties, and thermal shock resistance of the thermal insulation tile, and improves the brittleness of the thermal insulation tile; in the step of preparing the modified reinforced fiber, the polyimide fiber is surface-modified using silane coupling agent A-171 to improve the bonding performance between the polyimide fiber and the outer layer molded body and the phenolic aerogel, improve the stability of the thermal insulation tile during rapid temperature changes, and further improve the brittleness of the thermal insulation tile to avoid brittle fracture; in the step of preparing the composite molded body, the lower layer is set as the outer layer molded body, the middle layer is set as the modified reinforced fiber layer, and the upper layer is set as the The three-layer sandwich structure of the outer layer molding is used to prepare a composite molding; then in the step of preparing the impregnation solution, the phenolic aerogel and nano-tantalum boride are used to prepare the impregnation solution, and the composite molding is subjected to an impregnation and shaping treatment. The aforementioned technical means cooperate and work synergistically with each other, which can improve the brittleness of the material, avoid brittle fracture, and improve the high-temperature protection durability while effectively improving the bonding performance of the fiber skeleton and the phenolic resin material; effectively reduce the thermal stress problem of the insulation tile, avoid cracks or deformation of the insulation tile during rapid temperature changes, and further improve the mechanical properties and thermal insulation properties of the insulation tile.

[0122] Unless otherwise specified, all percentages used in the present invention are by mass.

[0123] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a phenolic aerogel composite thermal insulation tile, characterized in that: The method comprises the following steps: preparing an outer layer molded body, preparing a modified reinforcing fiber, preparing a composite molded body, preparing an impregnation liquid, and impregnating and shaping; The preparation of the outer layer molded body comprises the following steps: pre-modification and composite molding; The pre-modification method is that in an argon atmosphere environment, nano silicon carbide whiskers and short carbon fibers are treated with plasma to obtain pre-modified nano silicon carbide whiskers and pre-modified short carbon fibers; The composite molding method comprises the following steps: adding nano lightweight magnesium oxide, yttrium oxide, and octadecyl magnesium chloride into zirconium oxide sol, dispersing them uniformly, and obtaining a sol coating liquid; adding pre-modified nano silicon carbide whiskers and pre-modified short carbon fibers into the sol coating liquid, stirring them uniformly, and then standing and impregnating them to obtain a mixed slurry; introducing the mixed slurry into a mold, filtering and molding, and obtaining a molded body; and drying the molded body, and then heat-preserving and roasting it at 240-260° C. to obtain an outer layer molded body. The method for preparing the modified reinforcing fiber is: in an ethanol solution, a silane coupling agent A-171 is used to treat a polyimide fiber to prepare the modified reinforcing fiber; The method for preparing the composite molded body comprises: laying the modified reinforcing fiber layer on the outer layer molded body; then placing an outer layer molded body on the modified reinforcing fiber layer to obtain a preformed body; the preformed body is pressed after being wetted with deionized water, and dried and shaped to obtain a composite molded body; The method for preparing the impregnation solution is to add sodium bicarbonate, Tween-80 and nano-tantalum boride into deionized water and disperse them evenly; then add phenolic resin and silane coupling agent KH-550 and disperse them evenly to prepare the impregnation solution; The impregnation and shaping method comprises the following steps: impregnating the composite molded body into an impregnation liquid, vacuum impregnating, standing to shape, and calcining at 420-450° C. to obtain the phenolic aerogel composite insulation tile.

2. The method for preparing the phenolic aerogel composite thermal insulation tile according to claim 1, characterized in that: During the pre-modification, the distance between the nano silicon carbide whiskers or chopped carbon fibers and the discharge center in the plasma treatment device is maintained at 12-15 cm; The argon gas introduction rate is controlled to be 0.6-0.7 L / min, the plasma treatment frequency is 3-4 MHz, the discharge power is 300-400 W, and the plasma treatment time is 10-15 min.

3. The method for preparing the phenolic aerogel composite thermal insulation tile according to claim 1, characterized in that: In the pre-modification, the diameter of the nano-SiC whiskers is 100-120 nm and the length is 35-40 μm; The diameter of the chopped carbon fibers is 450-500 nm and the length is 10-13 mm.

4. The method for preparing the phenolic aerogel composite thermal insulation tile according to claim 1, characterized in that: In the composite molding, the weight ratio of the modified nano silicon carbide whisker, the pre-modified chopped carbon fiber, and the sol coating liquid is 3.5-4:1.2-1.5:35-40; Control the filtration thickness of the mixed slurry to 12-15mm; The heating rate to 240-260°C is 0.8-0.9°C / min, and the heat preservation and roasting time is 70-90min.

5. The method for preparing the phenolic aerogel composite thermal insulation tile according to claim 1, characterized in that: In the composite molding, the concentration of zirconium oxychloride in the zirconium oxide sol is 0.25-0.3 mol / L; The weight ratio of nano lightweight magnesium oxide, yttrium oxide, octadecyl magnesium chloride and zirconium oxide sol in the sol coating liquid is 3.5-4:0.15-0.18:0.5-0.6:100; The average particle size of nano lightweight magnesium oxide is 20-25nm.

6. The method for preparing the phenolic aerogel composite thermal insulation tile according to claim 1, characterized in that: The method for preparing the modified reinforced fiber comprises the following steps: adding the polyimide fiber into an ethanol solution, dispersing the fiber uniformly, heating the solution to 45-50° C., and dripping a silane coupling agent A-171 while maintaining the temperature; controlling the dripping time of the silane coupling agent A-171 to be 40-60 minutes; and after the dripping is completed, continuing the heat treatment for 4-5 hours, separating out the solid matter, and drying the solution to obtain the modified reinforced fiber.

7. The method for preparing the phenolic aerogel composite thermal insulation tile according to claim 1, characterized in that: In the preparation of the modified reinforced fiber, the volume concentration of the ethanol solution is 75-80%; The weight ratio of polyimide fiber, ethanol solution and silane coupling agent A-171 is 8-9:100:1.5-1.8; The diameter of the polyimide fiber is 6-7 μm and the length is 10-13 mm.

8. The method for preparing the phenolic aerogel composite thermal insulation tile according to claim 1, characterized in that: In the preparation of the composite molded body, the ply thickness of the modified reinforcing fiber is controlled to be 8-10 mm; The drying and setting temperature is 100-105℃ and the insulation time is 10-12h.

9. The method for preparing the phenolic aerogel composite thermal insulation tile according to claim 1, characterized in that: In the preparation of the impregnation solution, the weight ratio of sodium bicarbonate, Tween-80, nano-tantalum boride, deionized water, phenolic resin, and silane coupling agent KH-550 is 1.2-1.3:0.8-0.9:7-7.5:50-55:100-110:16-17; The phenolic resin is a phenolic resin prepolymer with a molecular weight of 300-400; The particle size of nano-tantalum boride is 40-50nm.

10. The method for preparing the phenolic aerogel composite thermal insulation tile according to claim 1, characterized in that: In the impregnation and shaping, the volume ratio of the composite molding to the impregnation liquid is 1:2-2.5; The method of static setting is to let it stand at room temperature for 10-12 hours, then raise the temperature to 90-95℃, keep it warm and let it stand for 5-6 hours; then lower the temperature to 40-45℃, keep it warm and let it stand for 10-12 hours; The heating rate to 420-450°C is 3-3.5°C / min, and the heat preservation and roasting time is 1.5-2h.

Citation Information

Patent Citations

  • Carbon-based lightweight thermal protection material as well as preparation method and application thereof

    CN107337474A

  • Preparation method of heat insulation material and heat insulation material prepared by method

    CN110629543A